The Feminine Reclaimed : The Idea of Woman in Spenser, Shakespeare, and Milton - Davies, Stevie (Book collections on Project MUSE., 1986)
The Feminine Reclaimed breaks new ground in the field of Renaissance scholarship. Stevie Davies considers the feminine principle as it was developed through the humanist and Neoplatonic revival of ancient classical learning and from this perspective approaches the major works of the three great literary figures of the English Renaissance -- Spenser, Shakespeare, and Milton. Through close, perceptive readings of their most crucial works, informed by a familiarity with the whole range of their context in the European literature and thought of their time, Stevie Davies is able to demonstrate the.